Strategies for energy efficiency renovation and evaluation system of existing residential building in hot summer and cold winter zone - M.Y. Lu; J. Ge; T.T. Shen; X.Y. Luo (International Association of Lowland Technology, 2015)
According to the climate characteristics in Hot Summer and Cold Winter (HSCW) zone, this study summarizes the special strategies for retrofitting the Existing Residential Buildings (ERB) in four aspects: envelop reformation, external environment improvement, energy saving behavior and renewable energy utilization. Then this study constructs the evaluation system frame of energy saving effect through 3 factors which are architecture design, construction and economic investment to comprehensively assess the practical effect of transforming. This research chooses a classical residential building in Huzhou as a case study and adopts the technologies to rebuild and uses the above evaluation system to figure out the most suitable reforming project. We hope our study about the reconstruction technologies and evaluation system can give some reference to renovation of existing residential buildings in other regions in China.